The correlation between nutritional status and CD8+ cell counts in the elderly after the second COVID-19 vaccination in Palembang, Indonesia - Khoirun Mukhsinin Putra; Nur Riviati; Eddy Mart Salim; Nova Kurniaty; Desti Paramita (Bahasa Indonesia, 2022)
Introduction: The SARS-CoV-2 virus is the cause of coronavirus illness (COVID-19). The WHO classified the outbreak a pandemic on March 9, 2020. The COVID-19 vaccine has been widely utilized to manage the pandemic. However, some high-risk conditions that can compromise the vaccine's efficacy require careful consideration. Patients over 60 years old are at a greater risk for COVID-19. Due to the involution of the thymus and the transformation of the cortex and medulla tissue into adipose tissue, CD8+ T cell numbers decline. In addition, undernutrition reduces the number of CD8+ T cells. The purpose of this study is to examine the relationship between nutritional status and CD8+ T cell counts in elderly patients following the second COVID-19 vaccination. Methods: This study is a pilot project employing a cross-sectional design. The sampling employed a technique of sequential sampling. On day 28, following the administration of the second vaccine, the Mini Nutritional Assessment (MNA) and the amount of CD8+ T cells in the blood were utilized to evaluate the nutrition status. Results: Between May and November of 2021, forty subjects were collected. The average number of CD8+ T cells was 517.32±41.67. Therefore, five people (12.5%) were at risk of malnutrition, whereas thirty-five (87.5%) had a normal nutritional status. Conclusion: There is a significant relationship between MNA and CD8+ levels (P<0.05) and a positive correlation between nutritional status and CD8+ T cell counts in the elderly who have received the second covid-19 vaccination in Palembang.